P PERSONAL CREATIVITY EFFECT ON BUSINESS PERFORMANCE WITH ENTREPRENEURIAL ORIENTATION AS INTERVENING VARIABLES IN EMBROIDERY INDUSTRY ENTERPRISES IN ACEH - kusdiarni, yuli yuli (Advances in Social Sciences Research Journal, 2019)
Personal creativity, business performance and entrepreneurial orientation are the most important parts for entrepreneurs in running their businesses. This study discusses the influence of personal creativity on business performance withmediation by entrepreneurial orientation. The purpose of this study is: first, to analyze the influence of personal creativity that is significant on entrepreneurial orientation; and second, to analyze the influence of personal creativity and entrepreneurial orientation which are partially and simultaneously significant towards business performance. The method used is distributing questionnaires to 200 embroidery industry entrepreneurs in Aceh as samples. The data analysis tool used is path analysis with SPSS version 22. The results of the analysis show that entrepreneurial orientation is a mediating variable between personal creativity and business performance.